Development and validation of ultra‐high‐performance liquid chromatography–mass spectrometry method for the determination of raloxifene and its phase II metabolites in plasma: Application to pharmacokinetic studies in rats. Issue 24 (20th November 2020) - Du, Ting; Sun, Rongjin; Li, Li; Ebuzoeme, Christabel; Bui, Dinh; Zheng, Zicong; Yin, Taijun; Liang, Dong; Hu, Ming; Gao, Song
Abstract: The aim of this study is to establish a reliable liquid chromatography–mass spectrometry method to simultaneously quantitate raloxifene, and its major metabolites, raloxifene‐6‐glucuronide, raloxifene‐4′‐glucuronide, and raloxifene‐6‐sulfate in rat plasma samples for pharmacokinetic studies. The separation of the analytes was achieved on a Waters BEH C18 column. Water (0.1% formic acid) and acetonitrile were used as the mobile phases for elution. A one‐step protein precipitation using a mixture solvent was applied for plasma sample preparation. The method was validated following the FDA guidance. The results showed that the linear range were 1.95–1000 nM for raloxifene‐6‐glucuronide, and raloxifene‐4′‐glucuronide, 0.195–100 nM for raloxifene‐6‐sulfate, and 0.195–200 nM for raloxifene, respectively. The lower limit of quantification was 1.95, 1.95, 0.195, and 0.195 nM for raloxifene‐6‐glucuronide, raloxifene‐4′‐glucuronide, raloxifene‐6‐sulfate, and raloxifene, respectively. Only 20 µl of plasma sample was required since the method is sensitive. The intra‐ and interday variance is <15% and the accuracy is within 85–115%. The variance of matrix effect and recovery were <15%. The method was successfully applied in a pharmacokinetic study in rats with oral administration of raloxifene.